Diagnosis of osteoarticular tuberculosis by immuno‐PCR assay based on mycobacterial antigen 85 complex detection. (5th November 2021) - Khan, A.; Singh, R.; Sharma, S.; Singh, V.; Sheoran, A.; Soni, A.; Dhull, V.; Gill, P.S.; Yadav, A.; Chaudhary, D.; Gupta, M.C.; Mehta, P.K.
Abstract: Diagnosis of osteoarticular tuberculosis (OATB) exhibits serious challenges owing to paucibacillary nature of specimens and localization of disease at sites that are difficult to access. We recently developed indirect immuno‐PCR (I‐PCR) and real‐time I‐PCR (RT‐I‐PCR) assays for the detection of mycobacterial antigen 85 complex (Ag85) in OATB patients. Detection limits for the purified Ag85 protein were found to be 1 and 41 fg ml −1 by I‐PCR and RT‐I‐PCR, respectively, which were at least 10 5 ‐fold lower than respective ELISA. While spiking synovial fluids of non‐TB control subjects with the purified Ag85 protein, LODs of 100 and 120 fg ml −1 were obtained by I‐PCR and RT‐I‐PCR, respectively, thus demonstrating the sample matrix effect. Sensitivities of 87·5 and 70·5% were observed in bodily fluids of confirmed ( n  = 8) and clinically suspected ( n  = 51) OATB cases, respectively, by I‐PCR, with a specificity of 93·9% ( n  = 33). Markedly, the sensitivities obtained by I‐PCR/RT‐I‐PCR were significantly higher ( P  < 0·05–0·01) than ELISA and GeneXpert assay ( n  = 30). However, no substantial difference in sensitivity was observed between the I‐PCR and RT‐I‐PCR assays. After further improving the accuracy of I‐PCR, this test may lead to development of an attractive diagnostic kit. Abstract : Significance and Impact of the Study: We designed immuno‐PCR (I‐PCR) assay based on mycobacterial Ag85 complex detection for early diagnosis of osteoarticular tuberculosis (OATB), which revealed a reasonably good sensitivity and specificity. Sensitivities obtained by I‐PCR were significantly higher than ELISA and GeneXpert. Additionally, real‐time I‐PCR (RT‐I‐PCR) was developed that detected a wide range of Ag85 concentration (0·75 pg ml −1 to 9 ng ml −1 ) within OATB specimens. No significant improvement in sensitivity was obtained by RT‐I‐PCR, compared with I‐PCR. Diagnostic accuracy of I‐PCR may be further enhanced by detecting a cocktail of antigens in OATB specimens. This study would improve the utility of existing algorithms in OATB diagnostics.